2022
DOI: 10.1177/07316844211068116
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of compressive strength of fiber-reinforced polymers-confined cylindrical concrete using artificial intelligence methods

Abstract: Compressive strength is the ability of materials to withstand loads without deformation or cracking. It is one of the most important criteria for evaluating the properties of concrete. The use of Fiber-Reinforced Polymers (FRP) to Strengthen concrete columns and as a supplement to improve some properties of concrete materials has received much attention in recent decades. Therefore, it is important to investigate and determine the compressive strength of confined concrete with FRP sheets. In this study, a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 125 publications
0
1
0
Order By: Relevance
“…In this section, the evaluation between the developed ML models and analytical models is discussed to define the reliability of the proposed models. In addition, the accuracy and reliability of the developed ML models has been verified by a recently developed ML model, which was given by Jamali et al [43]. Based on the results of the performance metrics of all the analytical as well as ML models, it can be concluded that the optimized GPR model has the highest precision, as indicated in Table 6.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this section, the evaluation between the developed ML models and analytical models is discussed to define the reliability of the proposed models. In addition, the accuracy and reliability of the developed ML models has been verified by a recently developed ML model, which was given by Jamali et al [43]. Based on the results of the performance metrics of all the analytical as well as ML models, it can be concluded that the optimized GPR model has the highest precision, as indicated in Table 6.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, the MAE, MAPE, and RMSE values of the model of Benzaid et al [48] are 119.08%, 138.20%, and 74.77% higher than those of the SVM model, whereas the R-value and NS value of the SVM model are 15.32% and 41.14% greater than those of the model of Benzaid et al [48]. Additionally, the R-value of the optimized GPR model is 1.11% higher than that of the model of Jamali et al [43], while the MAPE and RMSE values of the model of Jamali et al [43] are 25.69% and 116.18% greater than those of the optimized GPR model, respectively.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The compressive strength of FRP-confined concrete was investigated and determined by Jamali et al [73]. A large database of 1066 confined concrete cylinders with FRP sheets was collected.…”
Section: Compressive Strength Of Frp-confined Concretementioning
confidence: 99%
“…Especially in bridges, building reinforcement, and marine construction, pultruded GFRP has emerged as the optimal alternative to steel due to its excellent mechanical performance and environmental resistance [ 2 ]. These materials are typically employed as reinforcement (bars, sheets, and laminates) and pultruded load-bearing components (profiles) in combination with concrete [ 3 , 4 , 5 , 6 ]. The market share of FRP (fiber-reinforced polymer) profiles has increased rapidly in the last decade to reach USD 15.3 billion, which is 6.4% of the construction market [ 7 ].…”
Section: Introductionmentioning
confidence: 99%